Cost of occupational safety and health using circular number: 11/se/m/2019 on the rehabilitation work of the karajinan irrigation area - Paikun; Wisnu Resdiawan; Inge Sundaryani; Nurdin; Matthew Paul Cant (Nusa Putra University, 2020)
To minimize the number of work accidents in construction work, especially in irrigation work. Irrigation construction service providers must provide costs for occupational safety and health purposes taken from the total project costs. This study has the aim of knowing the amount of occupational safety and health costs required according to Circular Number 11/SE/M/2019 (SE19). The research was carried out using the literature study method where the stages of data analysis were compiling a list of risks that occurred, assessing risk, mitigating risk, calculating occupational safety and health costs with the price survey results and calculating the percentage of occupational safety and health costs to the contract. The results showed that 27 occupational accidents and safety risks were identified with 18 low risk categories and 9 moderate risks. The required occupational safety and health cost based on the contract is Rp. 11,961,000.00 while the cost based on the SE19 regulations is Rp. 18,350,000.00.